English Reading Material for Young Learner: How is It in the Classroom? - Rosmen; Syarif, Hermawati; Zainil, Yetty (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
This study investigated the English reading materials (ERM) for students of Sekolah Dasar Swasta (SDS: private elementary school) IKAL Medan. The purpose of this study was to assess the relevance of ERM to the needs of SDS IKAL Medan students, particularly Grade IV. This research was conducted as a content analysis study. It was an evaluation of the existing ERM from the existing English textbook, Grow with English: Book 4, published by Erlangga, 2015. Also, the theory or principle of effective ERM was reviewed to determine its feasibility. The data for this study came from an investigation of the existing ERM and the teacher interview results. The findings of this study indicated that the existing ERM does not meet Grade IV SDS IKAL Medan learners’ needs. In order to address the needs of the Grade IV students at SDS IKAL Medan, it was determined that new ERM were required. Thus, it is proposed that the English teacher should develop a suitable ERM that is relevant to the students’ needs and also related to the theory or principles of an effective reading material for English young learners.